PEMBERDAYAAN LANSIA BERBASIS KOMUNITAS MELALUI LAYANAN SOSIAL HOLISTIK DI UPT PSTW JEMBER - Puji Maulana; Moch. Arifudin; Asna Asna (Pandalungan: Jurnal Pengabdian kepada Masyarakat, 2026)
The increasing number of elderly people in Indonesia demands the availability of social services that can meet physical, psychological, social, and spiritual needs in an integrated manner. However, the implementation of elderly empowerment programs that integrate psychosocial counseling, spiritual support, activity therapy, and social participation in social service institutions is still limited. This community service activity aims to improve the psychosocial well-being of the elderly through a holistic empowerment program at the Jember Technical Implementation Unit for Social Services for the Elderly (UPT PSTW). The activity was implemented using an Asset-Based Community Development (ABCD) approach through the stages of preparation, discovery, dream, design, define, and destiny. The implementation results showed that the entire series of activities can be implemented collaboratively by involving managers, counselors, caregivers, volunteers, and the elderly. Although there are still limitations in human resources and supporting facilities, the asset-based approach can optimize the potential of institutions and communities in providing social services. This activity shows that the integration of psychosocial counseling, spiritual support, activity therapy, and social participation is a good practice that can be a reference for the development of elderly empowerment services in other social service institutions.